PEMANFAATAN DAUN PINUS (Pinus merkusii) SEBAGAI ADSORBEN DENGAN IMOBILISASI SILIKA GEL UNTUK MENYERAP LOGAM TIMBAL (Pb) - Putra Marjid, Rio
Pines (Pinus merkusii) contain cellulose and lignin compounds which can be utilized as adsorbent to absorb dissolved metals in water. Biosorbent produced from pines do not have a strong bond and easily to degrade so it needed to be strengthen by immobilization using silica gel. There are two biosorbent, first, biosorbent without treatment and second is biosorbent immobilized using silica gel. This research was presented to determine the ability of pine leaves to absorb metal lead (Pb). The optimum adsorption capacity condition for BWT is in the conditions of 0.149 mm particle size, biosorbent dose 20 g/L, contact time of 10 minutes, with initial concentration of 50 ppm, while for BTSG is in particle size of 0.149 mm, biosorbent dose 5 g/L, contact time of 30 minutes, with initial concentration of 50 ppm. BTSG biosorbent has a better performance than BWT. From the isotherm adsorption, obtained that the adsorption mechanism for BWT is monolayer and for BTSG is multilayer. Adsorption kinetics following second order kinetic models for BWT and BTSG. Isotherm adsorption was determined using the Langmuir and Freundlich equations whereas kinetic absorption was determined using the Lagergren equation.